Modification of media compositions for micropropagation of Acorus calamus L. - Aida Wulansari; Tri Muji Ermayanti; Erwin Al Hafiizh; Betalini Widhi Hapsari; Evan Maulana (Biogenesis: Jurnal Ilmiah Biologi, 2023)
Modification of medium composition is a critical step in tissue culture to find out the best medium formulation for micropropagation. Furthermore, reduction of some nutrients as well as sugar and plant growth regulator concentrations are an effort often done to make the production of seedlings more economic. The aim of the study was to modify media composition by reduction of macronutrients and sugar concentrations in combination with BAP for micropropagation of Acorus calamus. Experiments of Calamus micropropagation was established by culturing single shoots to MS medium with 100, 50, 33.3 and 25% macronutrients added with sugar at 30, 20, and 10 g/l in combination with 0, 0.5, and 1 mg/l BAP. Each medium treatment had nine replicates. Growth of culture was determined every week until 6 weeks of culture. Growth variable recorded was shoots numbers, leaf length, leaf numbers and root numbers. At six weeks of culture, chlorophyll content was also observed. The results showed that reduction of macronutrients and sugar did not influence shoot and leaf numbers in MS medium but required 0.5-1 mg/l BAP. Rooting is best in medium with no addition of BAP. Chlorophyll content decreased in the medium containing BAP in all reduced macronutrients and sugar concentrations. All plantlets survived in the field. Reduction of macronutrients and sugar can be applied for Calamus shoot culture. Cytokinin BAP is critical for shoot growth but this could be omitted for rooting. Therefore, this finding offered more choices in micropropagation of Calamus with low-cost production.